Identification of Recurrent Laryngeal Nerve and Parathyroid Glands Intraoperatively by Methylene Blue Spraying Technique - Zeena Noor eldeen Abdulrahman1, Waleed Qahtan Rajab1, Zainab jameel Ali2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Thyroid surgery has been associated with complications ranging from recurrent laryngeal nerve injury, inadvertent para- thyroidectomies to death. Improvement in thyroidectomy techniques have reduced the mortality rate to minimum, while morbidity remained a significant concern. Aims: This study aims to assess a method to identify recurrent laryngeal nerve and localize the parathyroid glands during thyroid surgery by using methylene blue stain which improve outcomes following thyroidectomy.Materials and methods : This a prospective cross- sectional study was performed on 48 adult patients of both sexes who presented to the surgical ward at Salah Al-Deen general hospital in Tikrit city between October 2017 and July 2018. Full medical history was taken and clinical examination was done to those who were suitable for surgery. After indirect larngyoscopic confirmation of normal vocal cord mobility, in addition hospital medical records were obtained including patient’s name, age, gender, residence, nature of thyroid disease, duration of thyroid disease, previous thyroid surgery, family history of thyroid disease and past medical history, relevant investigations like final histopathology ; all were chosen to undergo thyroidectomy, following superior but before inferior thyroid pedicles ligation, methylene blue dye, in a concentration of 2:8 and 1:10 of Methylene Blue: Normal Saline was sprayed over the thyroid lobe and perilobar area, in the region where recurrent laryngeal nerve is predictable to be found. Recurrent laryngeal nerve and parathyroid glands were identified and safe dissection of the thyroid without injuring these structures were ensured. Results: Recurrent laryngeal nerve was not stained in all cases, in contrast to the blue stained adjacent tissue. Within three minutes parathyroid glands washed out the dye and the yellow color was regained. Conclusions: Several techniques of recurrent laryngeal nerve and parathyroid glands identification were established , our study demonstrate that visual delineation of these structures by methylene blue dye spraying during dissection of thyroid is a simple, safe and effective method for localization and injury avoidance to both recurrent laryngeal nerve and parathyroid glands during thyroid surgery.